Economic analysis of the adoption of capsule endoscopy within the British NHS. (12th May 2020) - Lobo, Alan; Torrejon Torres, Rafael; McAlindon, Mark; Panter, Simon; Leonard, Catherine; van Lent, Nancy; Saunders, Rhodri
Abstract: Objective: Identification of a cost-effective treatment strategy is an unmet need in Crohn's disease (CD). Here we consider the patient outcomes and cost impact of pan-intestinal video capsule endoscopy (PVCE) in the English National Health Service (NHS). Design: An analysis of a protocolized CD care pathway, informed by guidelines and expert consensus, was performed in Microsoft Excel. Population, efficacy and safety data of treatments and monitoring modalities were identified using a structured PubMed review with English data prioritized. Costs were taken from the NHS and Payer Provided Services (PSS) 2016–17 tariffs for England and otherwise literature. Analysis was via a discrete-individual simulation with discounting at 3.5% per annum. Setting: NHS provider and PSS perspective Participants: 4000 simulated CD patients Interventions: PVCE versus colonoscopy ± magnetic resonance enterography (MRE) Main outcome measures: Costs in 2017 GBP and quality-adjusted life years (QALY) Results: The mean, total 20-year cost per patient was £42 266 with colonoscopy ± MRE and £38 043 with PVCE. PVCE incurred higher costs during the first 2 years due to higher treatment uptake. From year 3 onwards, costs were reduced due to fewer surgeries. Patients accrued 10.67 QALY with colonoscopy ± MRE and 10.96 with PVCE. PVCE dominated (less cost and higher QALY) colonoscopy ± MRE and was likely (>74%) to be considered cost-effective by the NHS. Results were similar if a lifetime time horizon was used. Conclusions: PVCE is likely to be a cost-effective alternative to colonoscopy ± MRE for CD surveillance. Switching to PVCE resulted in lower treatment costs and gave patients better quality of life.